THE ROLE OF PRAGMATIC MEANS IN ENGLISH PROFESSIONAL COMMUNICATION (Scientific journal of the Fergana State University, 2026)
This article analyzes the importance of pragmatic tools in ensuring the effectiveness of professional communication. In particular, the influence of the speaker's intention, the social position of the listener, the context of communication and the use of language units in the desired places in accordance with cultural factors is highlighted on a scientific basis. Examples analyze the role of pragmatic tools in various fields (medicine, pedagogy, jurisprudence and marketing).